Acute hypoxia increases the cerebral metabolic rate – a magnetic resonance imaging study. Issue 6 (June 2016) - Vestergaard, Mark B; Lindberg, Ulrich; Aachmann-Andersen, Niels Jacob; Lisbjerg, Kristian; Christensen, Søren Just; Law, Ian; Rasmussen, Peter; Olsen, Niels V; Larsson, Henrik BW
The aim of the present study was to examine changes in cerebral metabolism by magnetic resonance imaging of healthy subjects during inhalation of 10% O2 hypoxic air. Hypoxic exposure elevates cerebral perfusion, but its effect on energy metabolism has been less investigated. Magnetic resonance imaging techniques were used to measure global cerebral blood flow and the venous oxygen saturation in the sagittal sinus. Global cerebral metabolic rate of oxygen was quantified from cerebral blood flow and arteriovenous oxygen saturation difference. Concentrations of lactate, glutamate, N-acetylaspartate, creatine and phosphocreatine were measured in the visual cortex by magnetic resonance spectroscopy. Twenty-three young healthy males were scanned for 60 min during normoxia, followed by 40 min of breathing hypoxic air. Inhalation of hypoxic air resulted in an increase in cerebral blood flow of 15.5% ( p = 0.058), and an increase in cerebral metabolic rate of oxygen of 8.5% ( p = 0.035). Cerebral lactate concentration increased by 180.3% (p < 10 - 6 ), glutamate increased by 4.7% (p < 10 - 4 ) and creatine and phosphocreatine decreased by 15.2% ( p < 10 - 3 ). The N-acetylaspartate concentration was unchanged ( p = 0.36). In conclusion, acute hypoxia in healthy subjects increased perfusion and metabolic rate, which could represent an increase in neuronal activity. We conclude that marked changes in brain homeostasis occur in the healthy human brain during exposure to acute hypoxia.